Antibacterial efficacy of Salvadora persica as a cleansing teeth towards Streptococcus mutans and Lactobacilli colonies - Mahanani, Erlina Sih; Khamis, Mohd Fadhli; Arief, Erry Mochamad; Rippin, Siti Nabilah Mat; Rajion, Zainul Ahmad (Universitas Airlangga, 2012)
Salvadora persica is a traditional chewing stick for cleaning teeth that it is known Siwak. Several studies have demonstrated the antimicrobial effects of Salvadora persica. Purpose: This study was aimed to examine the effectiveness of Salvadora persica in several modified preparation against the salivary Streptoccocus mutans and Lactobacilli. Methods: A single-blind, randomized clinical trial study with crossover design was used. The study comprised of 5 groups, per group consisted of 14 healthy dental students who had good oral hygiene. Each participant was given 5 intervention to clean their teeth using, electric toothbrush modified with siwak, electric toothbrush with siwak toothpaste (colgate kayu sugi toothpaste), electric toothbrush with general toothpaste (colgate total toothpaste), original siwak chewing stick and normal saline. The wash out periode each intervention was 3 days. Patients’ saliva was used to quantify the levels of Streptococcus mutans and Lactobacilli using caries risk test (CRT) kit from Vivadent. Results: The results showed that there was a reduction in Streptococcus mutans and Lactobacilli risk score after cleansing different intervention except electric toothbrush modified with siwak. However, there was no significant difference for Streptococcus mutans (p=0.158) and Lactobacilli (p=0.396) risk score reduction when comparison was done between the groups. Conclusion: The original siwak chewing stick has antimicrobial effects similar to toothbrushing with general toothpaste and salvadora persica toothpaste. However, electric toothbrush modified with siwak has no effect on microbial reduction.